ANALISIS STRATEGI GURU DALAM MENUMBUHKAN KEMAMPUAN LITERASI SISWA KELAS V DI SDN GAJAH 02 - Fitria Rohandini; Sri Utaminingsih; Lintang Kironoratri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The purpose of this study is to describe the strategies used by teachers in growing the literacy skills of fifth grade students at SDN Gajah 02, Gajah District, Demak Regency. The research method used is qualitative. Research data collection is done through observation, interviews, and documentation. The research was conducted in the even semester of the 2021/2022 academic year. Research sources include class teachers and fifth grade students at SDN Gajah 02, Demak. Data checking was carried out using triangulation to increase the degree of confidence and accuracy of the data. Triangulation is done with three strategies, namely source triangulation, method triangulation, and time triangulation. The data analysis technique used is the Miles and Huberman analysis technique. The results showed that the strategies used by the teacher in growing the literacy skills of fifth grade students at SDN Gajah 02 were divided into three stages, namely there were five strategies applied at the habituation stage which aimed to familiarize students with reading and writing, at the development stage there were three strategies applied. Mrs. WK which aims to provide encouragement so that students have passion or interest and enthusiasm to carry out reading activities whenever and wherever, and at the stage of learning the strategy used by Mrs. WK is to encourage students to be able to take part in literacy competitions.